Anthropology : the exploration of human diversity - Kottak, Conrad Phillip (Boston : McGraw-Hill, 2002)
This text offers an introduction to the five sub-disciplines of anthropology: cultural, physical, archaeological, linguistic, and applied. It adopts an eclectic approach, and this edition includes coverage of race, gender and diversity, as well as a chapter on cultural exchange and survival.
Includes bibliographical references and indexes.
Keywords: Anthropology